The Strategy for Non-Special Education Teachers in the Habituation of Strengthening Character Education for Mental Retardation Students - Ahmad, Ahmad; Indrawadi, Junaidi; Suryanef, Suryanef; Erianjoni, Erianjoni (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to answer the phenomenon by analyzing the strategies of non-special education teachers in the habituation of strengthening educational character (PPK) in mentally retarded students at SLB Negeri 4 Jakarta at the elementary school level. This study uses a qualitative method with a case study approach. The sampling technique is purposive sampling. The data collection techniques used are observation, interviews, and documentation analysis. Triangulation of data sources was used to test the validity of the data in this study. The data analysis technique used is data reduction, data presentation, and conclusion. Of the three research questions including What are the strategies of non-special education teachers in habituation of strengthening educational character (PPK) in mentally retarded students at SLB Negeri 4 Jakarta at the elementary school level, why is this strategy successful, what are the advantages and obstacles of habituation of strengthening educational character and efforts to overcome obstacles the. The results of the study show that the strategies used by non-educational teachers are especially seen from the planning and implementation aspects by grouping them into classroom learning activities and activities outside the classroom. The success of non-educational teacher strategies, especially in strengthening educational character-building habits for mentally retarded children at SLB Negeri 4 Jakarta, is seen and influenced by various factors and approaches that have proven effective. Strengths, obstacles, and efforts to overcome these obstacles have also been compiled by dividing them into several points of discussion, which are certainly also in accordance with what is felt by non-special education teachers at SLB Negeri 4 Jakarta.